O movimento como fundamento da comunicação: experimentos de improvisação em dança - Monteiro, Maria Zélia Bacellar (2019)
The aim of this master’s dissertation is to research how improvisation in dance can complexify the ways in which the body communicates, as it destabilizes patterns of movement/thought, creating procedures to build connections and articulate unstable and unusual meanings. The grounding of this research comes from artistic creations directed by the Brazilian artist and researcher Klauss Vianna, and from experimentations tried by me, individually and collectively, since 1988. From a conceptual point of view, this dissertation relates debates proposed by the Corpomidia theory (KATZ; GREINER, 2015), which deny the understandings of the body as a recipient or instrument; to the concept of gesture defined by Manning (2016), and Simondon’s (2009) definition of individuation processes. The expected result is to contribute to studies that research the body’s means of communication from a point of view that is not purely instrumental, but as procedures to question, politically and philosophically, the possibility of new ways of living and forming affective bonds